f(x) = lnx-2/(x-1) -1
定义域 =(0,1) U (1,+∞)
f'(x) =1/x + 2/(x-1)^2 >0 ; x∈ (0,1) U (1,+∞)
=> f(x) 是递增函数
lim(x->0+) f(x)=lim(x->0+) [lnx-2/(x-1) -1] ->-∞
lim(x->1-)f(x) =lim(x->1-) [lnx-2/(x-1) -1] ->+∞
lim(x->1+) f(x) =lim(x->1+) [lnx-2/(x-1) -1] ->-∞
lim(x->+∞) f(x) =lim(x->+∞) [lnx-2/(x-1) -1] ->+∞
=>
只有2个实数根 x1< x2
x1∈(0, 1) , x2∈(1, +∞)
定义域 =(0,1) U (1,+∞)
f'(x) =1/x + 2/(x-1)^2 >0 ; x∈ (0,1) U (1,+∞)
=> f(x) 是递增函数
lim(x->0+) f(x)=lim(x->0+) [lnx-2/(x-1) -1] ->-∞
lim(x->1-)f(x) =lim(x->1-) [lnx-2/(x-1) -1] ->+∞
lim(x->1+) f(x) =lim(x->1+) [lnx-2/(x-1) -1] ->-∞
lim(x->+∞) f(x) =lim(x->+∞) [lnx-2/(x-1) -1] ->+∞
=>
只有2个实数根 x1< x2
x1∈(0, 1) , x2∈(1, +∞)